Assessing healthcare professional knowledge, attitudes, and practices on hypertension management. Announcing a new World Hypertension League resource. Issue 9 (September 2017) - Campbell, Norm R. C.; Dashdorj, Naranjargal; Baatarsuren, Uurtsaikh; Myanganbayar, Maral; Dashtseren, Myagmartseren; Unurjargal, Tsolmon; Zhang, Xin‐Hua; Veiga, Eugenia Velludo; Beheiry, Hind Mamoun; Mohan, Sailesh; Almustafa, Bader; Niebylski, Mark; et al.
Abstract : To assist hypertension control programs and specifically the development of training and education programs on hypertension for healthcare professionals, the World Hypertension League has developed a resource to assess knowledge, attitudes, and practices on hypertension management. The resource assesses: (1) the importance of hypertension as a clinical and public health risk; (2) education in national or international hypertension recommendations; (3) lifestyle causes of hypertension; (4) measurement of blood pressure, screening, and diagnosis of hypertension; (5) lifestyle therapy counseling; (6) cardiovascular risk assessment; (7) antihypertensive drug therapy; and (8) adherence to therapy. In addition, the resource assesses the attitudes and practices of healthcare professionals for task sharing/shifting, use of care algorithms, and use of registries with performance reporting functions. The resource is designed to help support the Global Hearts Alliance to provide standardized and enhanced hypertension control globally.